Cancer‐Cell‐Specific Nuclear‐Targeted Drug Delivery by Dual‐Ligand‐Modified Mesoporous Silica Nanoparticles. Issue 44 (1st October 2015) - Xiong, Lin; Du, Xin; Kleitz, Freddy; Qiao, Shi Zhang
Abstract : Mesoporous silica nanoparticles are modified with dual targeting ligands, i.e., folic acid and dexamethasone, to construct a cancer‐cell‐specific nuclear‐targeted delivery system. The resulting nanocarriers can not only enhance the inhibition efficacy of doxorubicin on Hela cells through active nucleus accumulation but also reduce toxic side effects on noncancer cells though receptor‐mediated selective cellular uptake.